2018
DOI: 10.1097/sap.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Refinement in the Creation of the Clitoris, Its Preputial Hood, and Labia Minora in Male-to-Female Transsexual Patients

Abstract: The proposed technique represents an aesthetic refinement of the previously described pedicled glans penis flap by allowing the creation of a sensate neoclitoris, its preputial hood, and labia minora with excellent outcomes in the same surgical stage as the sex reassignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…46 studies measured or reported on erogenous sensation of post‐surgical genitalia including the vulva, clitoris, anus, or mons pubis 11,13,18,19,30,33,35,44,45,48,51,66,67,70‐103 . General erogenous sensation ranged from 51.4% to 100% (median 97.7%) in 529 patients 11,13,30,74,80,88,89,91,100,101 . Only De Andrade (2013) reported a qualified scale for genital sensibility, receiving a 9.4/10 among 7 patients 75 .…”
Section: Resultsmentioning
confidence: 99%
“…46 studies measured or reported on erogenous sensation of post‐surgical genitalia including the vulva, clitoris, anus, or mons pubis 11,13,18,19,30,33,35,44,45,48,51,66,67,70‐103 . General erogenous sensation ranged from 51.4% to 100% (median 97.7%) in 529 patients 11,13,30,74,80,88,89,91,100,101 . Only De Andrade (2013) reported a qualified scale for genital sensibility, receiving a 9.4/10 among 7 patients 75 .…”
Section: Resultsmentioning
confidence: 99%
“…Reminding patients that there is no one “standard look” of a vulva may help when setting expectations on cosmetic outcomes. If sexual penetration is not a primary goal for the patient, a vulvoplasty can be a viable alternative for those that are at higher risk, as the procedure is less invasive and has been shown to have low complication rates 25 …”
Section: Discussionmentioning
confidence: 99%
“…If sexual penetration is not a primary goal for the patient, a vulvoplasty can be a viable alternative for those that are at higher risk, as the procedure is less invasive and has been shown to have low complication rates. 25…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…7 The construction of the labia minora from preputial tissues in uncircumcised patients and the preservation of the sensitivity of the labia minora are not new ideas. 8 In fact, the sensitive area on the inner surface of the labia minora was named as the "Chonburi flap" by Watanyusakul. Again, Watanyusakul 9,10 stated that an ideal vulva could not be reconstructed aesthetically with penile inversion and explained the necessary aesthetic gains.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are no exact guidelines describing how to reconstruct the clitoris, clitoral hood, or labia minora; therefore, the preferred technique depends on the surgeon, which may lead to different outcomes 7 . The construction of the labia minora from preputial tissues in uncircumcised patients and the preservation of the sensitivity of the labia minora are not new ideas 8 . In fact, the sensitive area on the inner surface of the labia minora was named as the “Chonburi flap” by Watanyusakul.…”
mentioning
confidence: 99%